Utilizing Drama Projects in Facilitating Speaking Proficiency Among Indonesian Non-English Department Students - Titin Purwaningtyas; Fury Yulia Damayanti; Rohmatul 'Adzima (English Language Education Department, Universitas Majalengka, 2025)
This study examines the integration of a drama project that can benefit students' speaking learning outcomes in the context of a higher education setting. Drama projects provide real-life material and a supportive learning environment that allows students to perform and interact with others as they practice the dialogue script. This study aims to (1) describe the implementation process of the drama project in the classroom and (2) examine students' motivation, creativity, and collaboration during its implementation. The participants were 35 intermediate-level students from non-English departments enrolled in an intensive English course at a private university in Surakarta. The research used a qualitative design. The researcher obtained the data through semi-structured interviews, an open-ended questionnaire, and classroom observation. The findings indicated that the drama project positively affected students’ speaking performance. The project also enhanced higher levels of motivation, creativity, and collaboration throughout the learning process. Meanwhile, students’ low performance is affected by several factors, including feeling shy and nervous about acting in front of the camera, limited editing skills, and time constraints. The research findings imply that integrating the drama project is beneficial for facilitating short-term intensive English programs that enhance students’ university communicative competence. Keywords: Drama, Project-Based Learning, Speaking Proficiency, Intensive English Course